2021
DOI: 10.1177/0253717621991210
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Problems in Children of Mothers who had Depression: A Cross-Sectional Study

Abstract: Background: Depression is a highly prevalent mental disorder. Maternal depression can adversely impact perinatal outcomes and child development, and can increase mental disorders for children and adolescents. Understanding the impact could lead to opportunities for early intervention and prevention. Methods: We selected 29 mothers attending a tertiary care setting for mental health, who had remitted following a depressive episode, and 35 control mothers. They rated their children’s behavior on the strengths an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Marçal ( 14 ) found that parental depression positively predicted child internalizing and externalizing problems based on a longitudinal study with Western samples. Parents with depression may have high levels of marital conflicts ( 15 ) and hostile parenting methods ( 16 ), contributing to high levels of child internalizing and externalizing problems ( 17 ). Additionally, according to the model of relationships between depressed mothers and child development discussed by Goodman and Gotlib ( 10 ), depressed parents may cause impairments in their child's later development.…”
Section: Parental Depression Internalizing and Externalizing Problems...mentioning
confidence: 99%
“…Moreover, Marçal ( 14 ) found that parental depression positively predicted child internalizing and externalizing problems based on a longitudinal study with Western samples. Parents with depression may have high levels of marital conflicts ( 15 ) and hostile parenting methods ( 16 ), contributing to high levels of child internalizing and externalizing problems ( 17 ). Additionally, according to the model of relationships between depressed mothers and child development discussed by Goodman and Gotlib ( 10 ), depressed parents may cause impairments in their child's later development.…”
Section: Parental Depression Internalizing and Externalizing Problems...mentioning
confidence: 99%
“…The study concluded that the measures are unsuitable for developmental screening due to their sub-optimal diagnostic accuracy. In addition, for the past two years, several studies have used the SDQ on children in India but have not investigated the psychometric properties of the measure [23][24][25][26][27][28]. However, it appears that the PEDS and SDQ have yet to be used together to screen children for developmental delay and SEL in India.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse emotions, such as worries, fear, guilt, shame, and embarrassment (Källquist & Salzmann‐Erikson, 2019; Reedtz et al, 2019) and social isolation and exclusion are common among these children (Yamamoto & Keogh, 2018). They are also at increased risk of behavioural and developmental disorders (Gladstone et al, 2011), educational underachievement (Källquist & Salzmann‐Erikson, 2019; Ng‐Knight et al, 2018) and physical and psychosocial health problems in their future life (Kallapiran & Jayanthini, 2021; Källquist & Salzmann‐Erikson, 2019; Radicke et al, 2021). Above all, caregiving to a mentally ill family member can be very challenging, leading to burnout and mental health issues, such as anxiety and depression in the caregivers (Zauszniewski & Bekhet, 2014).…”
Section: Introductionmentioning
confidence: 99%